Given that:
( x + x 2 + 1 ) ( y + y 2 + 1 ) = 1
Calculate: x + y
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used my instinct .........:) heehhee
Supposing x and y reals, we can make the following substitution: x = tan α , y = tan β ; α , β ∈ [ 0 , 2 π ) ( tan α + tan α 2 + 1 ) ( tan β + tan β 2 + 1 ) = 1 ( tan α + sec α ) ( tan β + sec β ) = 1 tan α tan β + tan α sec β + sec α sec β + sec α sec β = 1 sin α sin β + sin α + sin β + 1 = c o s α cos β cos ( α + β ) = 2 sin 2 α + β cos 2 α − β + 1 sin 2 2 α + β = − sin 2 α + β cos 2 α − β i) sin ( − 2 α + β ) = sin ( − 2 π − α + β ) ⇒ α = 2 − π + 2 k π or β = 2 − π + 2 k π (Out of the domain!) ii) sin 2 α + β = 0 ⇒ α + β = 2 k π Therefore: x + y = tan α + tan β = tan α + tan ( 2 k π − α ) = t a n α − t a n α = 0 .
Multiply the equation out to get x y + x y 2 + 1 + y x 2 + 1 + ( y 2 + 1 ) ( x 2 + 1 ) = 1
Square both sides to get x 2 y 2 + x 2 ( y 2 + 1 ) + y 2 ( x 2 + 1 ) + ( x 2 + 1 ) ( y 2 + 1 ) = 1
Simplify to get 4 x 2 y 2 + 2 x 2 + 2 y 2 + 1 = 1
Subtract 1 from both sides to get 4 x 2 y 2 + 2 x 2 + 2 y 2 = 0
The only way for this equation to be true is if x 2 = y 2 = 0 and only 0 2 = 0
So since x = y = 0 the solution is 0 + 0 = ∗ ∗ 0 ∗ ∗
That is not how we square both sides.
There are only 2 possible solution of (x,y) namely x=y or x≠y we assume the solution is x=y,so (x+√(x^2 +1))(x+√(x^2+1))=1 (x+√(x^2 +1))^2=1 √(x^2 +1)=1-x Then we get the equation is x^2+1=x^2+1-2x So we can getting x=0 So the solution is x=y=0
X+Y=0
x=0; y=0; just check it out!
Problem Loading...
Note Loading...
Set Loading...
Nice try, but please prove this problem!
We have:
( x 2 + 1 + x ) ( x 2 + 1 − x ) = 1
( y 2 + 1 + y ) ( y 2 + 1 − y ) = 1
So:
x 2 + 1 + x = y 2 + 1 − y ( ∗ )
y 2 + 1 + y = x 2 + 1 − x ( ∗ ∗ )
Calculate 2 sides of 2 equations ( ∗ ) and ( ∗ ∗ ) , erase all common terms, we have:
x + y = − x − y
⇔ 2 x + 2 y = 0
⇔ x + y = 0
Hence, x + y = 0